2021
DOI: 10.1007/s00204-021-03180-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the reduction in US mortality if cigarettes were largely replaced by e-cigarettes

Abstract: Background Recent estimates indicated substantially replacing cigarettes by e-cigarettes would, during 2016–2100, reduce US deaths and life-years lost (millions) by 6.6 and 86.7 (Optimistic Scenario) and 1.6 and 20.8 (Pessimistic). To provide additional insight we use alternative modelling based on a shorter period (1991–2040), four main smoking-associated diseases, deaths aged 30–79 years, and a full product history. We consider variations in: assumed effective dose of e-cigarettes versus cigare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The chemical composition of CC smoke has been well studied [6] and much is known about the harmfulness of smoking CCs [1]. Studies have indicated that ENDS use is less harmful than CC smoking [7][8][9][10][11] but there are still questions about the potential harmfulness of ENDS aerosols. These questions are rooted in the fact that much of our understanding regarding the harmfulness of cigarette smoking is founded on an understanding of the chemical constituents which are produced during combustion in the production of mainstream smoke.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition of CC smoke has been well studied [6] and much is known about the harmfulness of smoking CCs [1]. Studies have indicated that ENDS use is less harmful than CC smoking [7][8][9][10][11] but there are still questions about the potential harmfulness of ENDS aerosols. These questions are rooted in the fact that much of our understanding regarding the harmfulness of cigarette smoking is founded on an understanding of the chemical constituents which are produced during combustion in the production of mainstream smoke.…”
Section: Introductionmentioning
confidence: 99%
“…A challenge with the existing literature on ENDS and HnB products is that, as with other innovative products, there has been limited time to study their long-term harm. There are studies that estimate long-term consequences, such as Lee et al (2022), that estimate a substantial reduction in death even under pessimistic assumptions if cigarettes were largely replaced by ENDS. However, without longitudinal studies the long-term effects of ENDS and HnB products remain uncertain.…”
Section: Smoking and Nicotinementioning
confidence: 99%
“…[39][40][41][42][43][44][45] Should e-cigarettes prove helpful, reductions in smoking prevalence supported by them would provide large improvements in population health by greatly reducing smoking-related mortality. [46][47][48] It has been suggested that for nicotine products, including e-cigarettes, assessment of their harm reduction potential has to take into account three major factors-toxicity/harmfulness, appeal and dependence. 1 The harm reduction potential, when considering the ability of e-cigarettes to reduce harm in current smokers, hits a 'sweet spot' when appeal and dependence are high and when toxicity and harmfulness are low.…”
Section: Introductionmentioning
confidence: 99%
“…Observational data also support a link between ENDS use and quitting smoking 39–45 . Should e‐cigarettes prove helpful, reductions in smoking prevalence supported by them would provide large improvements in population health by greatly reducing smoking‐related mortality 46–48 …”
Section: Introductionmentioning
confidence: 99%